Linguistic Landscape on Food and Beverage Signboards in Binjai City - Anggita Pratiwi; T. Silvana Sinar; Rahmadsyah Rangkuti; Rusdi Noor Rosa (Jurnal Pemberdayaan Masyarakat, 2025)
The linguistic landscape in the food and beverage scene of Binjai City, North Sumatra, reflects and celebrates the city's rich cultural diversity and flavorful cuisine. This study explores the linguistic landscape of the food and beverage sector in Binjai City, highlighting how language use in public signage reflects both local culture and global influences. As the city experiences rapid urban growth and increasing exposure to global trends, its signage offers valuable insights into the intersection of language, identity, and commerce. The research aimed to (1) analyze the linguistic features of food and beverage signboards and (2) examine the reasons behind language choices made by business owners. Using a qualitative methodology, comprising observation and documentation, the study investigated 96 signboards. The results showed that 67.71% were monolingual, predominantly in Indonesian, while 32.29% were bilingual, with a notable presence of English. The inclusion of English was not merely decorative but served a strategic purpose: to project an image of modernity, professionalism, and appeal to consumers influenced by global trends. These findings reveal how Binjai's linguistic landscape is shaped by a dynamic interplay between preserving local identity and embracing international appeal. This research enhances our understanding of how globalization influences linguistic practices in urban settings, offering a valuable case study that informs cross-cultural discussions about language, identity, and commerce.